Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (New feminist perspective series, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques